USABILITY MEASUREMENT OF GOOGLE CLASSROOM APPLICATIONS AS E-LEARNING FOR STUDENTS OF DEPARTMENT OF BUILDING ENGINEERING EDUCATION IKIP GUNUNG SITOLI - Envilwan Harefa (ISER (Indonesian Science Education Research), 2020)
This study aims to determine the level of usefulness of the Google Classroom application by distributing questionnaires to respondents. This research was a case study research. The results of the questionnaire were measured using a Likert scale. Google classroom was an open source application from Google that can be used for learning systems or can be called e-learning. This application is a new application and still a few are using it in the learning system in schools and colleges. From the measurement results it will be known the level of usability value of the google classroom application which was used as e-learning for students in the IKIP Gunungsitoli Building Engineering Education study program.